Osteoprotegerin inhibits the development of osteolytic bone disease in multiple myeloma. - Croucher, P; Shipman, C; Lippitt, J; Perry, M; Asosingh, K; Hijzen, A; Brabbs, A; van Beek, E; Holen, I; Skerry, T; Dunstan, C; Russell, G; et al. (2001)
Multiple myeloma is a B-cell malignancy characterized by the accumulation of plasma cells in the bone marrow and the development of osteolytic bone disease. The present study demonstrates that myeloma cells express the critical osteoclastogenic factor RANKL (the ligand for receptor activator of NF-kappa B). Injection of 5T2MM myeloma cells into C57BL/KaLwRij mice resulted in the development of bone disease characterized by a significant decrease in cancellous bone volume in the tibial and femoral metaphyses, an increase in osteoclast formation, and radiologic evidence of osteolytic bone lesions. Dual-energy x-ray absorptiometry demonstrated a decrease in bone mineral density (BMD) at each of these sites. Treatment of mice with established myeloma with recombinant osteoprotegerin (OPG) protein, the soluble decoy receptor for RANKL, prevented the development of lytic bone lesions. OPG treatment was associated with preservation of cancellous bone volume and inhibition of osteoclast formation. OPG also promoted an increase in femoral, tibial, and vertebral BMD. These data suggest that the RANKL/RANK/OPG system may play a critical role in the development of osteolytic bone disease in multiple myeloma and that targeting this system may have therapeutic potential.